2008
DOI: 10.1371/journal.ppat.1000060
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of West Nile Virus Modulates Sensitivity to Antibody-Mediated Neutralization

Abstract: West Nile virions incorporate 180 envelope (E) proteins that orchestrate the process of virus entry and are the primary target of neutralizing antibodies. The E proteins of newly synthesized West Nile virus (WNV) are organized into trimeric spikes composed of pre-membrane (prM) and E protein heterodimers. During egress, immature virions undergo a protease-mediated cleavage of prM that results in a reorganization of E protein into the pseudo-icosahedral arrangement characteristic of mature virions. While cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
288
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(317 citation statements)
references
References 48 publications
29
288
0
Order By: Relevance
“…Internal plasticity and motions of the capsid proteins can allow access to buried regions, which often play an important role in the viral life cycle [46]. Indeed, multiple antibodies against picornaviruses and flaviviruses that bind to normally inaccessible sites on the viral capsid were shown to be highly neutralizing [47][48][49][50][51][52]. For rhinoviruses and polioviruses, buried regions of internal VP4 protein are transiently exposed due to the capsid "breathing" and are targeted by neutralizing mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Internal plasticity and motions of the capsid proteins can allow access to buried regions, which often play an important role in the viral life cycle [46]. Indeed, multiple antibodies against picornaviruses and flaviviruses that bind to normally inaccessible sites on the viral capsid were shown to be highly neutralizing [47][48][49][50][51][52]. For rhinoviruses and polioviruses, buried regions of internal VP4 protein are transiently exposed due to the capsid "breathing" and are targeted by neutralizing mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Partially mature virions can be infectious, although the extent of prM cleavage required for infectivity is not known (reviewed in reference 39). The efficiency of virion maturation has the potential to impact virus binding, environmental conditions required to trigger membrane fusion, cellular tropism, and sensitivity to antibodymediated neutralization (40)(41)(42)(43)(44).…”
Section: Flavivirusesmentioning
confidence: 99%
“…However, newer studies proved that even fully immature virions of flaviviruses can cause infection by antibodies [70,71]. Regarding partially immature virions, multiple studies have shown that they can also be infectious [17,72]. It seems that the mature part of these virions is responsible for cell binding and entry after which the further processing of remaining prM may take place inside the cell.…”
Section: Replication Cyclementioning
confidence: 99%
“…There are also many structurally distinct epitopes, not easily accessible to certain neutralizing antibodies. It is characteristic that studies showed a reduction of the neutralizing ability of antibodies correlated to the maturation state of WNV: Maturation reduces the accessibility of some of the epitopes on the virion [17]. Thus, these antibodies cannot efficiently neutralize the virus even if at high levels of concentration.…”
Section: Adaptive Response Includes Humoral and Cellular Responsementioning
confidence: 99%
See 1 more Smart Citation